Effects of electrical aging on the structural and physicochemical properties of crosslinked polyethylene (XLPE) cable insulation material. (1st March 2022) - Hedir, Abdallah; Slimani, Ferhat; Moudoud, Mustapha; Lamrous, Omar; Durmus, Ali; Fofana, Issouf
Abstract: The aim of this work is to highlight the evolution of physico-chemical properties of peroxide crosslinked polyethylene (XLPE) insulation material exposed to electrical aging. Specific analysis and characterization studies were carried out to determine the effect of electrical aging on different samples at micro and macro levels. Based on the analytical investigations, it was shown that electrical aging yielded significant changes in the chemical and thermal characteristics of XLPE. It was also showed that property loss increased with the aging time.